Unseen Dangers: The Effects of Micro- and Nanoplastics on Human Reproductive Health - A Narrative Review - Kumar, Naina (Recent Advances in Inflammation & Allergy Drug Discovery, 2025)
Micro(nano)plastics (MNPs) have become pervasive environmental pollutants due to widespread use and inadequate waste management practices. These tiny particles infiltrate various ecosystems, including the human body, raising significant concerns about their potential health effects. Of particular concern is their impact on human reproductive health, with emerging research indicating MNPs' ability to breach biological barriers, accumulate in reproductive organs, and potentially reach the placenta. A comprehensive literature search spanning from July 2015 to July 2024 was conducted across prominent electronic databases, including PubMed, Scopus, Web of Science, and Google Scholar. Key search terms such as “micro and nanoplastics,” “microplastics and male reproductive health,” “microplastics and female reproductive health,” “transgenerational spread of microplastics,” and “microplastics and fetal health” were used to identify relevant studies published in peer-reviewed journals, books, and reputable conference proceedings. Selection criteria favoured review articles, original research papers, meta-analyses, and authoritative texts published in English. Synthesized findings from these studies were critically analysed to underscore their potential impacts on reproductive health. The accumulating evidence emphasizes the urgent need for further research to fully grasp the risks posed by MNPs to human reproductive health. Effective mitigation strategies are essential to minimize exposure and mitigate potential long-term consequences. Policy interventions aimed at enhancing waste management practices and regulating plastic usage are crucial to curb the environmental spread of MNPs and safeguard human reproductive health effectively.
Keywords: Fertility